Dietary intakes and anthropometric indices in women with hirsutism and healthy women of reproductive age - Reihaneh Rahimi; Hadis Varaee; Shirin Amini (Mashhad University of Medical Sciences, 2021)
Introduction: Hirsutism refers to the abnormal and excessive hair growth, with a pattern similar to the male pattern in women. It is possible that dietary intake and body weight are associated with hirsutism, so the present study was conducted with aim to evaluate and compare dietary intake and anthropometric indices in women with hirsutism and healthy women. Methods: This case-control study was performed in 2020 on 84 women with hirsutism (case) and 168 healthy women (control) in Shoushtar city. Participants were assessed by the food frequency questionnaire, about the usual number of units consumed from each food group, including cereals, dairy products, protein, fruits and vegetables in the last year. Data were analyzed by SPSS statistical software (version 19) and independent t-test, Mann-Whitney and Chi-square tests. P < 0.05 was considered statistically significant. Results: Women with hirsutism had significantly higher weight (P = 0.019) and BMI (P = 0.018) than the control group. Consumption of high and medium-fat dairy (P = 0.034) and ice cream (P = 0.041), cakes and biscuits (P = 0.049) was significantly higher in hirsutism group compared to the controls. Conclusions: Reducing the consumption of medium and high fat dairy products along with a healthy lifestyle and maintaining a normal weight has an effective role in prevention of hirsutism.